A Mixed-Method Study on the Perceptions of Quality Management and Sustainability in Malaysian Hotel Industry - Sin, Kit Yeng; Abang Azlan, Mohamad; Lo, May Chiun (2021)
Rising trend of sustainability within tourism especially hotel industries remain ambiguous in many different areas of academic research and business. Nonetheless, contemporary relevance of quality practices and sustainability in the hotel industries has increased lately. This paper examined hotel quality managers (HQMs) perceptions of quality management and sustainability via the sequential-mixed methods approach, to bridge the gaps in the existing literature on the connection between pertinent variables. Therefore, in Phase 1 ten HQMs were deliberately selected and interviewed to perceive their views on quality management and the relationship between various quality management constructs towards sustainable performance. Phase 1 revealed that business ethics emerged as a new dimension, which needed to be emphasised. Subsequently, the qualitative results were utilised to design the hypotheses for 300 HQMs’ quantitative surveys in Phase 2. The obtained survey data was analysed via the Partial Least Square-Structural Equation Models (PLS-SEM) to determine a list of hypotheses related to the impacts of key constructs. The present study depicted a significant and positive mediating connection between the HQMs perspective of quality management, business principles, and sustainable performance.